2021
DOI: 10.3390/land10101085
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Behaviors toward the Use of Public and Private Green Space during the COVID-19 Pandemic in Iran

Abstract: This paper reports the results of an exploratory study carried out in Birjand, Iran, during the first year of the COVID-19 pandemic. The aim of the study was to explore the behavioral change in the use and the motivation to visit a green space (public or private) during the pandemic as compared to the pre-pandemic period, the effect of green spaces (private and public) on users’ feelings, the relations between the extent to which the access to green spaces was missed, and characteristics of respondents and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 104 publications
1
27
0
1
Order By: Relevance
“…Values associated with parks could be subject to environmental characteristics and social conditions as they often emerge from unique experiences in certain places ( Brown et al, 2015 , Chen et al, 2020 , Dickinson and Hobbs, 2017 , Hull et al, 1994 , Ives et al, 2017 ). During the COVID-19 pandemic when social distancing and home quarantine were recommended, the health and psychological benefits of urban parks became more salient as people were in need of being outside of home for mental rejuvenation, companion seeking, and physical activity ( Addas and Maghrabi, 2022 , Fagerholm et al, 2021 , Heo et al, 2021 , Khalilnezhad et al, 2021 , Noszczyk et al, 2022 , Reid et al, 2022 , Spano et al, 2021 , Ugolini et al, 2020 ). Although urban parks appear to be crucial to physical and mental wellbeing, decrease in usage or desire to visit was found to result from concerns about viral transmission, especially in places that tend to be crowded and at times when COVID cases were surging ( Addas and Maghrabi, 2022 , Fagerholm et al, 2021 , Larson et al, 2022 , Lopez et al, 2020 , Pan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Values associated with parks could be subject to environmental characteristics and social conditions as they often emerge from unique experiences in certain places ( Brown et al, 2015 , Chen et al, 2020 , Dickinson and Hobbs, 2017 , Hull et al, 1994 , Ives et al, 2017 ). During the COVID-19 pandemic when social distancing and home quarantine were recommended, the health and psychological benefits of urban parks became more salient as people were in need of being outside of home for mental rejuvenation, companion seeking, and physical activity ( Addas and Maghrabi, 2022 , Fagerholm et al, 2021 , Heo et al, 2021 , Khalilnezhad et al, 2021 , Noszczyk et al, 2022 , Reid et al, 2022 , Spano et al, 2021 , Ugolini et al, 2020 ). Although urban parks appear to be crucial to physical and mental wellbeing, decrease in usage or desire to visit was found to result from concerns about viral transmission, especially in places that tend to be crowded and at times when COVID cases were surging ( Addas and Maghrabi, 2022 , Fagerholm et al, 2021 , Larson et al, 2022 , Lopez et al, 2020 , Pan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A lot of pieces of evidence have shown that the unavailability and absence of UGSs, social isolation, and blockades during COVID-19 have a negative impact on mental health [13], presenting varying degrees of anxiety, anger, fear, irritability, reduced well-being, and other negative emotions [14][15][16], and increasing the risk of mental health disorders [17]. On the other hand, exposure to blue-green space is beneficial for physical and mental health [18,19], relieves stress [3], reduces anxiety, improves attention recovery [20], and increases well-being and satisfaction. To some extent, it increases motivation to exercise and enhances physical activity, thus reducing diseases such as obesity, hypertension, and hyperlipidemia [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Less affected were those who live in a house with its own garden, which allowed for an outdoor stay in a "safe" environment. The positive influence of one's own gardens has also been documented from Italy (Spano et al 2021), Brazil (Marques et al 2021) or Iran (Khalilnezhad et al 2021). Also Lõhmus et al (2021) found that more greenery around the home is associated with fewer symptoms of depression and anxiety.…”
Section: Discussionmentioning
confidence: 83%
“…The results of our study suggest that the deterioration of physical condition and mental well-being during the lockdown was more declared by women. The findings of an Iranian study (Khalilnezhad et al 2021) indicate that natural areas were also missing from women during the restrictions associated with the COVID-19 pandemic. Roe et al (2013) also point to the greater sensitivity of women.…”
Section: Discussionmentioning
confidence: 99%